Inter-rater agreement of the Quality of Life-Alzheimer’s Disease (QoL-AD) self-rating and proxy rating scale: secondary analysis of RightTimePlaceCare data - Römhild, Josephine; Fleischer, Steffen; Meyer, Gabriele; Stephan, Astrid; Zwakhalen, Sandra; Leino-Kilpi, Helena; Zabalegui, Adelaida; Saks, Kai; Soto-Martin, Maria; Sutcliffe, Caroline; Rahm Hallberg, Ingalill; Berg, Almuth (Health and quality of life outcomes, 2018)
Background To assess the quality of life of people with dementia, measures are required for self-rating by the person with dementia, and for proxy rating by others. The Quality of Life in Alzheimer’s Disease scale (QoL-AD) is available in two versions, QoL-AD-SR (self-rating) and QoL-AD-PR (proxy rating). The aim of our study was to analyse the inter-rater agreement between self- and proxy ratings, in terms of both the total score and the items, including an analysis specific to care setting, and to identify factors associated with this agreement. Methods Cross-sectional QoL-AD data from the 7th Framework European RightTimePlaceCare study were analysed. A total of 1330 cases were included: n = 854 receiving home care and n = 476 receiving institutional long-term nursing care. The proxy raters were informal carers (home care) and best-informed professional carers (institutional long-term nursing care). Inter-rater agreement was investigated using Bland-Altman plots for the QoL-AD total score and by weighted kappa statistics for single items. Associations were investigated by regression analysis. Results The overall QoL-AD assessment of those with dementia revealed a mean value of 33.2 points, and the proxy ratings revealed a mean value of 29.8 points. The Bland-Altman plots revealed a poor agreement between self- and proxy ratings for the overall sample and for both care settings. With one exception (item ‘Marriage’ weighted kappa 0.26), the weighted kappa values for the single QoL-AD items were below 0.20, indicating poor agreement. Home care setting, dementia-related behavioural and psychological symptoms, and the functional status of the person with dementia, along with the caregiver burden, were associated with the level of agreement. Only the home care setting was associated with an increase larger than the predefined acceptable difference between self- and proxy ratings. Conclusions Proxy quality of life ratings from professional and informal carers appear to be lower than the self-ratings of those with dementia. QoL-AD-SR and QoL-AD-PR are therefore not interchangeable, as the inter-rater agreement differs distinctly. Thus, a proxy rating should be judged as a complementary perspective for a self-assessment of quality of life by those with dementia, rather than as a valid substitute.